Augmentation of Hepatitis B Virus-Specific Cellular Immunity with Programmed Death Receptor-1/Programmed Death Receptor-L1 Blockade in Hepatitis B Virus and HIV/Hepatitis B Virus Coinfected Patients Treated with Adefovir - Sherman, Amy C. (Mary Ann Liebert, Inc., 2013)
The immunological parameters leading to viral persistence in chronic hepatitis B (CHB) are not clearly established. We analyzed HBV-specific immunoregulatory mechanisms in HIV-infected and HIV-uninfected HBeAg(+) CHB patients to determine (1) the roles of immunoregulatory pathways, (2) the effect of anti-HBV therapy on immunoregulatory pathways, and (3) the role of immunomodulatory therapy to overcome the effect of T regulatory cells (Tregs, CD4(+)CD25(+)FoxP3(+)) in HBV-infected individuals. A prospective, double blind, randomized, placebo-controlled trial treated HBV (HIV(+/–))-infected patients with adefovir 10 mg daily or placebo for 48 weeks. HBV viral load (VL), immunophenotying, and functional studies were performed at multiple time points. Suppression of HBV VL with adefovir leads to decreased peripheral expansion of Tregs. While declining, Tregs significantly inhibit cytokine-secreting HBV-specific CD8(+) T cell responses over 48 weeks of anti-HBV adefovir therapy (p<0.05). A large proportion of these Tregs express programmed death receptor-1 (PD-1), blockade of which in vitro leads to improved cytokine-secreting HBV-specific CD8(+) T cell responses, particularly in HIV/HBV-coinfected patients (p<0.05). Peripheral expansion of Treg levels correlated with HBV viral load and decreased HBV-specific CD8(+) T cells. PD-1 blockade increased survival of HBV-specific CD8(+) T cells, removing the inhibitory effect of PD-1(+) peripheral Tregs. Hence therapies involving PD-1 blockade in combination with directly acting antivirals should be investigated to reduce the need for life-long directly acting antiviral therapy.